2002
DOI: 10.1086/341002
|View full text |Cite
|
Sign up to set email alerts
|

The Slope of the Black Hole Mass versus Velocity Dispersion Correlation

Abstract: Observations of nearby galaxies reveal a strong correlation between the mass of the central dark object M BH and the velocity dispersion of the host galaxy, of the form logðM BH =M Þ ¼ þ logð = 0 Þ; however, published estimates of the slope span a wide range (3.75-5.3). Merritt & Ferrarese have argued that low slopes (d4) arise because of neglect of random measurement errors in the dispersions and an incorrect choice for the dispersion of the Milky Way Galaxy. We show that these explanations and several others… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

166
3,201
16
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,481 publications
(3,384 citation statements)
references
References 71 publications
166
3,201
16
1
Order By: Relevance
“…From FWHM(Hβ) and the AGN's optical continuum luminosity, the black hole mass was estimated to be ∼ 1.6 × 10 5 M , while the stellar velocity dispersion is 36 ± 5 km s −1 . With this black hole mass estimate, POX 52 falls almost exactly on an extrapolation of the local M − σ relation of Tremaine et al (2002).…”
Section: Can the Stellar Velocity Dispersions Of Quasar Host Galaxiesmentioning
confidence: 54%
“…From FWHM(Hβ) and the AGN's optical continuum luminosity, the black hole mass was estimated to be ∼ 1.6 × 10 5 M , while the stellar velocity dispersion is 36 ± 5 km s −1 . With this black hole mass estimate, POX 52 falls almost exactly on an extrapolation of the local M − σ relation of Tremaine et al (2002).…”
Section: Can the Stellar Velocity Dispersions Of Quasar Host Galaxiesmentioning
confidence: 54%
“…1, it is found that radio-quiet AGNs follow the M bh -σ relation defined by Tremaine et al (2002) but with a larger scatter. However, the radio-loud AGNs and NLS1s seemed not to follow this relation.…”
Section: Resultsmentioning
confidence: 82%
“…For nearby inactive galaxies, there exists a tight correlation (hereafter M bh − σ relation) M bh = 10 8.13 (σ/(200kms −1 )) 4.02 M (Tremaine et al 2002). Whether all kinds of AGNs follow this relation or not is still a matter to debate.…”
Section: Introductionmentioning
confidence: 99%
“…It will be easy to understand Seyfert and LINER activities in elliptical galaxies, such as the host galaxies of the most powerful AGNs (quasars) are usually the massive elliptical galaxies (Floyd et al 2004), that is because the recent discovery of a tight relation between bulge velocity dispersion and black hole mass, which strongly suggests that massive black holes are ubiquitous and scale with the bulge masses (Ho & Kormendy 2000;Tremaine et al 2002). While the pure star-forming activities in elliptical galaxies are especially rare, the nature and triggering mechanism are still open questions.…”
Section: Resultsmentioning
confidence: 99%